Government of Tripura Development Department Approach Paper for the Medium Term Investment Plan During 1978-83 and Draft Annual Plan 1978-79 Vol. II - Planning Commission (Planning Commission, 1978)
Most of them do not own any land and remain seasonally unemployed. This is contributing to further inequality. Another important factor which hinders the generation of income is the high percentage of dependent population. It has been estimated by the 1971 Census that 50.77% of the total population in Tripura are dependent. Furthermore, it has been estimated that about 16,500 tribal families practise shifting cultivation even now. Thus the high percentage of moral population, high rate of dependency, small operational holdings, heavy pressure on land, acute under-employment and unemployment and uneconomic shifting cultivation combine together to hinder economic growth in rural areas. Hence, the lot of the people below the poverty line remains almost unchanged. Planning is a continuous process and each plan is a milestone in its long arduous journey to reach the ultimate goal of maximum well-being of the individual. In the third decade of planning, within the constraints of resources and prescribed objectives, many perceptible and imperceptible plan achievements have been made yet much remains to be done. As the Fifth Five Year Plan terminates, the new plan generates yet new expectations with a new direction.
Approach Paper for the Medium Term Investment Plan During 1978-83 and Draft Annual Plan 1978-79 Vol. II
Government of Tripura